2021
DOI: 10.3390/jcm10153302
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Neurostimulation Methods for Acute and Preventive Migraine Treatment—A Narrative Review

Abstract: Neurostimulation methods have now been studied for more than 20 years in migraine treatment. They can be divided into invasive and non-invasive methods. In this narrative review, the non-invasive methods are presented. The most commonly studied and used methods are vagal nerve stimulation, electric peripheral nerve stimulation, transcranial magnetic stimulation, and transcranial direct current stimulation. Other stimulation techniques, including mechanical stimulation, play only a minor role. Nearly all method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 59 publications
(63 reference statements)
1
9
0
4
Order By: Relevance
“…In a recent narrative review, it was concluded that the data on the prophylactic efficacy of tDCS in CM were conflicting [16]. This has already been discussed previously, and the positive results of the present study can be explained by the homogeneity of our population, despite the limitation of the sample size.…”
Section: Suggestions For Future Researchsupporting
confidence: 61%
See 2 more Smart Citations
“…In a recent narrative review, it was concluded that the data on the prophylactic efficacy of tDCS in CM were conflicting [16]. This has already been discussed previously, and the positive results of the present study can be explained by the homogeneity of our population, despite the limitation of the sample size.…”
Section: Suggestions For Future Researchsupporting
confidence: 61%
“…In CM, central sensitization or long-term changes in brain plasticity may alter the modulatory systems of nociception [4][5][6][7][8][9][10]. These alterations have led to develop, for prophylactic purpose, invasive and non-invasive neuromodulation techniques such as occipital nerve stimulation (ONS), repetitive transcranial magnetic stimulation (rTMS) or transcranial direct current stimulation (tDCS) [11][12][13][14][15][16][17]. ONS involves a surgical implantation of electrodes and pulse generator by a specialized team, while rTMS requires costly equipment and iterative hospital sessions for the patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of high-potential alternative approaches to treatment of migraine is neurostimulation [4] and particularly repetitive transcranial magnetic stimulation (rTMS) [5]. The efficacy of this method has been confirmed for acute and preventive migraine treatment [6,7]. Another significant advantage of TMS is the absence of side effects [8].…”
Section: Introductionmentioning
confidence: 99%
“…The existing paradigms of TMS efficacy in depression [11] and secondary headaches [12] are based on the application of neuroimaging methods, particularly functional magnetic resonance imaging (fMRI) which is a promising tool for assessing interactions of the brain's neural networks in migraine patients as well [13][14][15]. As we know, migraine is characterized by various changes in functional connectivity (FC) in the brain's neural networks, which mostly result in pain perception disorder and the inadequate response to pain [16].…”
Section: Introductionmentioning
confidence: 99%